THE SPECIES OF RASTRELLIGER IN THE JAWA SEA, THEIR TAXONOMY AND MORPHOMETRY (PERCIFORMES, SCOMBRIDAE) - Sujastani, Tatang (Marine Research in Indonesia, 1976)
Analyses of morphometric data suggest that there are two species within the genus Rastrelliger, namely brachysoma and kanagurta. Rastrelliger neglectus is considered to be a synonym of R. brachysoma. Both species exhibit intraspecific geographical variations in some of their morphological characters. The characters that exhibit sexual dimorphisms, strong allometric growth, and geographical   variations   are   described. The description of the genus and a key to the species are given.